Green bonds as an instrument for financing in Europe - Frydrych, Sylwia (Ekonomia i Prawo. Economics and Law, 2021)
Motivation: The interest in sustainable, socially, environmentally and climatically stable development of the economy is growing. At the same time, issuers and investors are looking for financial instruments with which they can achieve their investment goals. The idea of the green bond market is to develop debt instruments in financing projects contributing to ecologically sustainable development, which should have a direct impact on the development of technologies and practices in the area of resource use that contribute to limiting adverse climate change. Bonds for financing or refinancing renewable energy sources and increasing energy efficiency are seen as a natural part of the transformation of the global economy. Aim: The purpose of the article is to present an analysis and goals of green bond market in Europe based on currency of issue, geographic structure, issue period, sectors and issue targets as well as major stock exchanges on which green bonds are listed. Results: Relevant data on the green bond market in Europe was analyzed and the objectives of issuing green debt finance in particular sectors by number of emission were identified. It was verified that green bonds, which are listed only on one stock exchange, mainly the Scandinavian one, have a lower average value of the issue.